Barriers to BIM Adoption in Brazil - Arrotéia, Aline V.; Freitas, Raissa C.; Melhado, Silvio B. (Frontiers in Built Environment, 2021)
Purpose: The research goal was to investigate the main barriers faced by a large Brazilian construction company in their efforts to thoroughly implement BIM. This study focused on the analysis of understanding the barriers to BIM adoption and the usage of 3/4 dimensions (3D/4D) on the development of an infrastructure project. Research methodology: The research methodology was exploratory and qualitative, carried out through a single-case study approach made upon bibliographical research, company document analysis, project document analysis, interviews, informal conversations, and observations. The research methodology was developed in six months (from June to December 2019) divided into three main phases: phase 1: definition and design; phase 2: preparation and collection; phase 3: data analysis and conclusion. Data collection was developed using a semistructured research protocol with two different semistructured questionnaires: the first questionnaire aimed at collecting data regarding BIM implementation in the company’s organizational context; the second one focused on the understanding of BIM adoption in the project and on the investigation of the main barriers related to the usage of 3D and 4D modeling in the project studied. Findings: Regarding BIM implementation in the company, although the company studied is a construction company in the infrastructure sector, BIM was considered more efficient in the design phase and flawed in the construction phase. Findings have shown that BIM has improved the information management of the design itself and its interface with the construction phase. In relation to the usage of BIM in the project, a more collaborative work environment was noticed due to the effectiveness of communication between the design and construction teams on the job site. With respect to the usage of 3D/4D modeling in the project studied, the difficulties in extracting information from the 3D model have disabled the usage of 4D modeling during the construction phase. Therefore, the difficulties reported were identified as an opportunity to map deficiencies in the BIM model in order to define parameters for the new project proposals and to automate the process of receiving the model and checking for inconsistencies or lack of information. Implications for Research and Practice: The case study is an example that BIM as a technological tool is not able to promote an integrated design and construction interface by itself. It is necessary to integrate BIM as an integrated process with structured management methods and tools. From our perspective, we understand that contracts should change, including construction stakeholders in the very beginning of the design process fostering collaboration across stakeholders such as designers, design and construction managers, suppliers, and subcontractors, thereby achieving a higher level of improvement potentially carried on by the new technologies allied to management practices. With regard to the nature of this article, it is important to make it clear that the results from this study were based on the Brazilian construction industry only. Limitations: The research is a single-case study; therefore, the findings cannot be generalized. Most of the data were dependent on the interviewees’ self-reported perceptions. We suggest new studies should be conducted with other construction companies in the Brazilian context, comparing companies with different organizational structures and sizes and other types of projects.